1988
DOI: 10.1001/jama.1988.03720130034026
|View full text |Cite
|
Sign up to set email alerts
|

The Stability of Early Specialty Preferences Among US Medical School Graduates in 1983

Abstract: Medical graduates in 1983 were in preclinical training when the Graduate Medical Education National Advisory Committee forecast a surplus of 70,000 physicians by 1990. Among the problems identified was the nuclear role of medical schools in affecting specialty choices. To understand this role further, the current study determined the stability and evolution of specialty preferences between the time of the Medical College Admission Test and the senior year of medical school. The study included 10,321 US medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…[23][24][25] Some of the predictive variables we identified in our study have been described elsewhere, though the reported effects sometimes conflict. These include age, 13 marital status, 13 having a societal orientation and volunteering in a developing country.…”
Section: E4mentioning
confidence: 98%
“…[23][24][25] Some of the predictive variables we identified in our study have been described elsewhere, though the reported effects sometimes conflict. These include age, 13 marital status, 13 having a societal orientation and volunteering in a developing country.…”
Section: E4mentioning
confidence: 98%
“…While some previous studies suggest up to 80% of medical students declare a specialty choice at graduation that differs from their anticipated specialty choice at the time of matriculation (Markert 1983;Babbott et al 1988;Brooks 1991;Forouzan and Hojat 1993;McLaughlin et al 1993;Fincher and Lewis 1999;Novielli et al 2001) other studies suggest that most specialty choices are made early and are stable (Zeldow et al 1992). Previous longitudinal studies suggest that the stability of specialty choice over time varies by gender (Babbott et al 1988;Forouzan and Hojat 1993;McLaughlin et al 1993;Novielli et al 2001), specialty choice (Markert 1983;Babbott et al 1988;Zeldow et al 1992;Forouzan and Hojat 1993;McLaughlin et al 1993;Novielli et al 2001), clerkship performance (McLaughlin et al 1993;Novielli et al 2001), personal values (Hojat et al 1998;Fincher and Lewis 1999;Connelly et al 2003), income expectations (Rosenthal et al 1992;Novielli et al 2001), and role models (Connelly et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Previous longitudinal studies suggest that the stability of specialty choice over time varies by gender (Babbott et al 1988;Forouzan and Hojat 1993;McLaughlin et al 1993;Novielli et al 2001), specialty choice (Markert 1983;Babbott et al 1988;Zeldow et al 1992;Forouzan and Hojat 1993;McLaughlin et al 1993;Novielli et al 2001), clerkship performance (McLaughlin et al 1993;Novielli et al 2001), personal values (Hojat et al 1998;Fincher and Lewis 1999;Connelly et al 2003), income expectations (Rosenthal et al 1992;Novielli et al 2001), and role models (Connelly et al 2003). Although these studies provide some insight into the factors associated with students changing their specialty preference during medical school most were conducted over a decade ago and several relied on single institution data.…”
Section: Introductionmentioning
confidence: 99%
“…The early clinical experience is likely an opportune time to begin such interventions because upon starting medical school up to 82% of students indicate interest in a specific specialty, but only 20-45% ultimately choose a residency in that specialty [4]. Others have shown that up to 80% change their specialty preferences from the time they take their medical school entrance examination until their final year of medical school [5]. …”
Section: Introductionmentioning
confidence: 99%